Negative electrode composition, negative electrode, and secondary battery

JP2025030959AActive Publication Date: 2025-03-07NIPPON PAPER IND CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023136702
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-03-07
Estimated Expiration
2043-08-25

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、ケイ素系の負極活物質を含む負極において、充放電の繰り返しによる劣化を抑制することができ、容量維持率などの電池性能に優れた二次電池を得ることが可能な負極用組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030959000001
    Figure 2025030959000001
  • Figure 2025030959000002
    Figure 2025030959000002
  • Figure 2025030959000003
    Figure 2025030959000003
Patent Text Reader

Abstract

To provide a negative electrode composition that can inhibit deterioration due to repeated charging and discharging and that can be used to obtain a secondary battery with excellent battery performance, such as a capacity retention rate in a negative electrode containing silicon-based negative electrode active material.SOLUTION: The negative electrode composition contains a silicon-based negative electrode active material and a dispersant. The dispersant contains a lignin component that includes a lignin derivative. The lignin derivative has a functional group as shown in the following formula (1). The S content in the functional group is 0.1 to 7.0 mass%. Formula (1):-SO3M (In the formula, M indicates a hydrogen atom, a monovalent metal, or a divalent metal.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode composition used in the negative electrode of a secondary battery, and to a negative electrode and a secondary battery using the same. [Background technology]

[0002] In recent years, the rapid spread of small portable devices such as smartphones and tablets, as well as stationary storage batteries, has led to an increasing demand for small batteries with high energy density to power them.

[0003] Generally, graphite-based materials are used for the negative electrodes of lithium-ion secondary batteries, but the theoretical capacity of graphite-based materials is 372 mAh / g (LiC6), which is currently approaching its limit.

[0004] Furthermore, in order to improve the energy density of lithium-ion secondary batteries, it is necessary to select new materials. Therefore, materials made by alloying lithium with silicon, tin, etc., which have the second lowest potential and large specific capacity after carbon and lithium, are attracting attention.

[0005] Among these materials, silicon can absorb up to 4.4 lithium atoms per silicon atom in molar ratio, and theoretically, it can obtain a capacity about 10 times that of graphite-based carbon materials. However, when silicon particles absorb lithium, their volume expands by about 3 to 4 times, and the problem is that repeated charging and discharging causes deterioration and a decrease in capacity. A detailed analysis of this phenomenon has confirmed that when lithium is inserted into an active material containing silicon, the volume expansion causes fine cracks in the electrode, and the electrolyte penetrates into these fine cracks to form a new coating (SEI layer). At this time, irreversible capacity that cannot be restored is generated, and as a result, the battery capacity decreases. This phenomenon appears in the change in charge and discharge efficiency during the cycle. In particular, the decrease in cycle efficiency in the early stage of the cycle, where the volume change is large, has a significant impact on the life of the battery when combined with a positive electrode with high charge and discharge efficiency. Therefore, when using an active material containing silicon, it is an important issue to minimize the adverse effects associated with the change in electrode structure due to this volume expansion.

[0006] Patent Document 1 describes that a negative electrode is manufactured by applying a negative electrode mixture slurry containing an electrode active material containing silicon, a lignin sulfonate, and a conductive assistant to a current collector and drying the mixture to form a coating film (negative electrode active material layer) of the negative electrode mixture on the current collector. It also describes that a battery using the negative electrode manufactured in this manner has excellent capacity characteristics.

[0007] However, the negative electrode mixture slurry described in the examples of Patent Document 1 contains too high a proportion of components other than the active material (lignin, carboxymethyl cellulose, and conductive additive), and therefore a battery obtained using a negative electrode produced with this slurry is considered to have too low performance to withstand practical use. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] European Patent Application Publication No. 3544099 Summary of the Invention [Problem to be solved by the invention]

[0009] The silicon-based negative electrode active material contained in the negative electrode mixture slurry described in the examples of Patent Document 1 is about 60% on a solids basis. However, when the amount of silicon-based negative electrode active material is large, deterioration due to repeated charging and discharging progresses, and there is a problem that satisfactory battery characteristics cannot be obtained.

[0010] An object of the present invention is to provide a composition for a negative electrode that can suppress deterioration due to repeated charging and discharging in a negative electrode containing a silicon-based negative electrode active material, and can provide a secondary battery with excellent battery performance such as capacity retention rate. [Means for solving the problem]

[0011] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by containing a silicon-based negative electrode active material and a specific dispersant.

[0012] The present invention provides the following: (1) A composition for a negative electrode of a secondary battery, comprising: a silicon-based negative electrode active material; and a dispersant, the dispersant containing a lignin component including a lignin derivative, the lignin derivative having a functional group represented by the following formula (1), and a S content in the functional group of 0.1 to 7.0 mass %. Formula (1):-SO3M (In the formula, M represents a hydrogen atom, a monovalent metal, or a divalent metal.) (2) The negative electrode composition according to (1), wherein the lignin component has a weight average molecular weight of 6,000 to 35,000, and a value obtained by dividing the weight average molecular weight by the number average molecular weight is 1.5 to 3.1. (3) The negative electrode composition according to (1) or (2), wherein the amount of extractable components per solid content of the lignin component is 0.01 to 2.5 mass%, the amount of methoxy groups per solid content of the lignin component is 3 to 18 mass%, and the mass ratio of the amount of extractable components per solid content of the lignin component to the amount of methoxy groups per solid content of the lignin component is 0.001 to 0.25. (4) The negative electrode composition according to (1) or (2), wherein a total yield of decomposition products by alkaline nitrobenzene oxidation is 15% or less per solid content of the lignin component. (5) A negative electrode for a secondary battery, comprising a negative electrode active material layer containing the negative electrode composition according to (1) or (2), a negative electrode binder, and a conductive assistant. (6) A secondary battery comprising the negative electrode according to (5). (7) The negative electrode composition according to (1) or (2), wherein the secondary battery is a lithium ion battery. Effect of the Invention

[0013] According to the present invention, it is possible to provide a negative electrode composition that can suppress deterioration due to repeated charging and discharging in a negative electrode containing a silicon-based negative electrode active material, and that can provide a secondary battery with excellent battery performance, such as capacity retention rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below. In the present invention, "to" includes the end values. That is, "X to Y" includes the values ​​X and Y at both ends.

[0015] <<Composition for negative electrode>> The negative electrode composition of the present invention contains a silicon-based negative electrode active material and a dispersant, the dispersant contains a lignin component including a lignin derivative, the lignin derivative has a functional group represented by the following formula (1), and the S content in the functional group is 0.1 to 7.0 mass %, and is used for the negative electrode of a secondary battery. Formula (1):-SO3M (In the formula, M represents a hydrogen atom, a monovalent metal, or a divalent metal.)

[0016] (Negative electrode active material) The composition for a negative electrode of the present invention contains a silicon-based negative electrode active material. Examples of the silicon-based negative electrode active material include silicon-based compounds such as silicon particles or silicon oxide particles. From the viewpoint of having a relatively small volume expansion rate during charge and discharge and obtaining high cycle characteristics, silicon oxide particles are preferred. Note that the silicon oxide in the present invention is SiO x (represented by (0 < x ≤ 2)). Further, in the present invention, from the viewpoint of imparting conductivity, a composite of a silicon-based compound and a graphite material such as graphite (natural graphite, artificial graphite, etc.), coke, or carbon fiber is more suitable as the negative electrode active material.

[0017] When the negative electrode active material is a composite of a silicon-based compound and a graphite material, the mixing ratio of the graphite material to the silicon-based compound is preferably from 10:90 to 90:10, more preferably from 50:50 to 80:20.

[0018] The composition for a negative electrode of the present invention may also contain, as the negative electrode active material, other active materials other than the silicon-based negative electrode active material and the graphite material used as necessary. Examples of other active materials include elements capable of forming an alloy with lithium, such as elements such as Al, Sn, Ag, Bi, Mg, Zn, In, Ge, Pb, and Ti; compounds containing elements capable of forming an alloy with lithium; composites of elements capable of forming an alloy with lithium and the compounds, and carbon and / or the graphite material, or nitrides containing lithium, etc. can be exemplified.

[0019] (Dispersant) The dispersant used in the present invention contains a lignin component containing a lignin derivative, the lignin derivative has a functional group represented by the following formula (1), and the S content in the functional group is 0.1 to 7.0% by mass. Formula (1): -SO3M (In the formula, M represents a hydrogen atom, a monovalent metal, or a divalent metal) Note that in the present invention, the dispersant is mainly used for the purpose of dispersing a silicon-based negative electrode active material in a dispersion medium or a negative electrode mixture composition.

[0020] (Lignin component) The dispersant used in the present invention contains a lignin component, and the lignin component contains at least a lignin derivative.

[0021] (Lignin derivatives) In this specification, the lignin derivative means a decomposition product of lignin, a derivative of lignin, or a derivative of a decomposition product of lignin. The lignin derivative may be in a powder form or a liquid form. The method for preparing a liquid lignin component is not particularly limited, but an example of the method is to dissolve a powdered lignin component in a suitable solvent (e.g., water, an aqueous sodium hydroxide solution, etc.) to obtain a liquid lignin component.

[0022] Lignin derivatives are usually derived from woody biomass and are classified into several types with different structures and physical properties depending on the processing method. Examples of lignin derivatives include lignin sulfonic acid, lignin sulfonate, kraft lignin, soda lignin, soda-anthraquinone lignin, organosolv lignin, explosive lignin, sulfuric acid lignin, and decomposition products thereof.

[0023] The lignin derivative is preferably modified from the viewpoint of improving the dispersibility of the silicon-based negative electrode active material. The types of modification include modification by alkali treatment, alkaline oxygen treatment, oxidation treatment using active oxygen species such as ozone and hydrogen peroxide, and modification of aromatic nuclei by sulfomethylation, and the like. From the viewpoint of improving the dispersibility of the silicon-based negative electrode active material, it is preferable to include those modified by alkali treatment, alkaline oxygen treatment, and sulfomethylation treatment. Sulfomethylated lignin can be obtained by sulfomethylating raw lignin, and the raw material can be kraft lignin, soda lignin, soda-anthraquinone lignin, organosolv lignin, explosive lignin, lignin sulfonate, sulfuric acid lignin, and their decomposition products, as well as their derivatives. The lignin derivative may be one type or a combination of two or more types. Since there is a relationship that the higher the degree of modification, the lower the total decomposition product yield by alkaline nitrobenzene oxidation, the degree of modification can be known by measuring the total decomposition product yield.

[0024] The lignin derivative used in the present invention preferably has a functional group (sulfo group) represented by the following formula (1), and from the viewpoint of improving the adsorptivity to the silicon-based negative electrode active material, the S content in the functional group is 0.1 to 7.0 mass%, preferably 0.1 to 6.0 mass%, and more preferably 0.1 to 5.0 mass%. If the S content is too high, there is a risk that the adsorptivity of the lignin to the silicon-based negative electrode active material will deteriorate. Formula (1): -SO3M (wherein M represents a hydrogen atom, a monovalent metal, or a divalent metal)

[0025] (S content) Here, the S content in the functional group refers to the content of sulfur atoms contained in the functional group relative to the solid content of the lignin derivative, and is specifically a value calculated by the following formula (2). Formula (2): S content (mass%) = total S content (mass%) - inorganic S content (mass%) In formula (2), the total S content and inorganic S content of the lignin derivative both indicate the S content relative to the solid content of the lignin derivative. In formula (2), the total S content is the total S content contained in the lignin derivative and can be quantified by ICP atomic emission spectrometry. The inorganic S content can be calculated from the total amount of the SO3 ion content, SO4 ion content, and S2O3 ion content quantified by ion chromatography.

[0026] (Weight average molecular weight) The weight-average molecular weight of the lignin component used in the present invention is preferably 6,000 to 35,000, more preferably 6,000 to 30,000, and even more preferably 6,000 to 25,000. If the weight-average molecular weight is greater than the above upper limit, the dispersibility of the silicon-based negative electrode active material may deteriorate.

[0027] (Polydispersity (weight average molecular weight / number average molecular weight)) The value obtained by dividing the weight average molecular weight by the number average molecular weight of the lignin component used in the present invention (also referred to as "polydispersity") is preferably 1.5 to 3.1, more preferably 1.5 to 2.5. If the polydispersity is greater than the upper limit, the dispersibility of the silicon-based negative electrode active material may deteriorate.

[0028] In the present invention, the weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The GPC measurement may be performed under the following conditions by a known method using pullulan as a conversion factor. Measuring device: Tosoh Columns used: Shodex Column OH-pak SB-806HQ, SB-804HQ, SB-802.5HQ Eluent: 1.0% sodium tetraborate, 0.3% isopropyl alcohol in water Eluent flow rate; 1.00mL / min Column temperature: 50°C Measurement sample concentration: 0.2% by mass Standard substance: Pullulan (Showa Denko) Detector: RI detector (manufactured by Tosoh) Calibration curve; Pullulan standard

[0029] (extracted component) The lignin component preferably contains an extractive component. In this specification, the extractive component is an extractive component of a plant (for example, a plant used as a pulp raw material, preferably wood of a plant of the genus Cryptomeria japonica, a plant of the genus Chamaecyparis obtusifolia, a plant of the genus Pinus serrata, a plant of the genus Larch, a plant of the genus Abies serrata, or a plant of the genus Eucalyptus), and is usually a trace component that is measured and identified by an extraction treatment of wood using an organic solvent. Among the extractive components, those having a phenolic hydroxyl group or a carboxyl group can also be obtained by extraction using an alkali. The extractive components are usually determining factors of wood physical properties such as color, odor, durability, adhesiveness, and biological activity, and are said to be components that chemically characterize wood. After the skeleton is formed by the deposition of cellulose and hemicellulose and the deposition of lignin, a tree is completed as a biological material only after the accumulation of extractive components linked to the formation of heartwood. Examples of organic solvents used to obtain the extractive components include hexane, benzene, ether, acetone, and alcohol. The content of the extractive components in wood is usually about 5% or less.

[0030] Extracted components usually contain low molecular weight compounds. Many of them are secondary metabolites with molecular weights of several thousand or less, and are generally very diverse, but are roughly classified into aromatic extracted components and terpenoids. Examples of aromatic extracted components include flavonoids, tannins, lignans, and stilbenes. Extracted components contain at least one selected from these.

[0031] Flavonoids are a general term for compounds having a diphenylpropane (C6-C3-C6) skeleton, and examples thereof include flavones, flavanones, chalcones, aurone, isoflavones, catechins, and leucoanthocyanidins. Tannins may be either hydrolyzable tannins or condensed tannins. Hydrolyzable tannins are tannins having a structure in which a phenolic carboxylic acid such as gallic acid is ester-bonded to a nucleus such as glucose, and examples thereof include gallotannins and ellagitannins. Hydrolyzable tannins can be decomposed into simple fragments by hydrolysis with acids, alkalis, etc., and when gallotannins and ellagitannins are hydrolyzed, gallic acid and ellagic acid are obtained, respectively. Condensed tannins include, for example, amorphous polymers whose precursors are catechins or leucoanthocyanidins.

[0032] Examples of lignans include lignans and related substances. Lignans (resinols) have a structure with a C6-C3-C3-C6 skeleton in which phenylpropane units, the same as the structural units of lignin, are carbon-carbon bonded between the β-positions of the side chains. Unlike lignin, they have an asymmetric carbon in the molecule and are optically active. Examples of lignan-related substances include norlignans, which have a C6-C3-C2-C6 skeleton with one less carbon atom than the lignin skeleton. Stilbenes may be any compound having an α,β-diphenylethylene skeleton.

[0033] Terpenoids may be any series of compounds in which two or more isoprene units (C5H8) are linked in a chain or ring. Terpenoids consisting of 2, 3, 4, and 6 isoprenoid units are called monoterpenes (10 carbon atoms), sesquiterpenes (15 carbon atoms), diterpenes (20 carbon atoms: for example, abietic acid), and triterpenes (30 carbon atoms), respectively, but any of these may be used.

[0034] Extractives have various physiological activities depending on the basic carbon skeleton and substituents of the extractives, such as biological activity against microorganisms, insects, and plants ("Resistance of wood to biological deterioration by extractives," Wood Conservation 34(2), 48-54, 2008), improvement of wood durability, inhibitory effects on human health, and inhibitory effects on chemical and physical processing of wood (e.g. pulping, bleaching, cement hardening).

[0035] (Extracted components / lignin components (mass ratio)) In the lignin component, the mass ratio of the amount of the extracted component to the amount of the methoxy group per solid content of the lignin component is preferably 0.001 to 0.25, more preferably 0.005 to 0.2, and even more preferably 0.01 to 0.15, from the viewpoint of highly orienting the lignin and the extracted component in the negative electrode. By having the mass ratio in the above range, the lignin and the extracted component can be highly oriented in the negative electrode. If the mass ratio is too large, the amount of the extracted component as an impurity increases, and the battery performance decreases, and if it is too small, the lignin and the extracted component cannot be oriented in the negative electrode.

[0036] The extractable components may affect the orientation of the negative electrode components, particularly with lignin. In addition, since methoxy groups bonded to aromatic nuclei are generally present in the structure of lignin, the amount of methoxy groups is an indicator of the content of lignin derivatives. Therefore, it can be said that the above mass ratio represents a balance for highly orienting the lignin and the extractable components in the negative electrode.

[0037] (Amount of extracted components) The amount of the extracted component per solid content of the lignin component is preferably 0.01 to 2.5 mass %, more preferably 0.1 to 2.0 mass %, from the viewpoint of affecting the orientation of the negative electrode components, particularly with the lignin.

[0038] (Methoxy group amount) The amount of methoxy groups per solid content of the lignin component is preferably 3 to 18% by mass, more preferably 5 to 15% by mass, from the viewpoint of using high-purity lignin. Since lignin generally has a methoxy group bonded to an aromatic nucleus in its structure, the amount of methoxy groups is an index of the content of lignin and lignin derivatives, i.e., the purity of lignin and lignin derivatives.

[0039] The amount of methoxy groups can be measured by the Viebock and Schwappach method for quantifying methoxy groups (see "Lignin Chemical Research Methods", pp. 336-340, 1994, published by Uni Publishing Co., Ltd.). The amount of extractable components can be measured by the method for measuring hexane extractable substances described in JIS K 0102:2019.

[0040] (Total Decomposition Product Yield) The total decomposition product yield of the lignin component by alkaline nitrobenzene oxidation (also simply referred to as "total decomposition product yield") is preferably 15% or less, more preferably 2% to 13%, from the viewpoint of improving the dispersibility of materials other than CMC contained in the negative electrode mixture composition. When the total decomposition product yield is within the above range, the dispersibility of materials other than CMC contained in the negative electrode mixture composition can be improved, and the battery performance can be improved. If the total decomposition product yield is too high, the dispersibility of materials other than CMC contained in the negative electrode mixture composition becomes insufficient, and the battery performance deteriorates. On the other hand, if the total decomposition product yield is too low, the degree of modification of lignin is too high, and the characteristics of lignin are lost, and various performances derived from lignin cannot be exhibited. Note that the lower the total decomposition product yield, the higher the degree of modification of lignin. Here, the total decomposition product yield can be quantified by the method described in "Plant Cell Wall Experimental Method" (see "Plant Cell Wall Experimental Method", pp. 128-131, 2016, published by Hirosaki University Press). The total decomposition product yield can be calculated from the ratio (w / w%) of the total weight of the six decomposition products (p-hydroxybenzaldehyde, p-hydroxybenzoic acid, vanillin, vanillic acid, syringaldehyde, and syringic acid) obtained by the measurement to the solid content of the sample.

[0041] (Lignosulfonic acid, lignosulfonate salts) Lignosulfonic acid and lignosulfonates are lignin derivatives having a sulfo group, which are prepared from lignocellulose raw materials through a sulfite treatment. Examples of methods for preparing lignosulfonic acid and lignosulfonates include a method in which the lignocellulose raw materials or lignin itself is subjected to a sulfite treatment, and preferably a method in which the lignocellulose raw materials or lignin itself is subjected to a sulfite cooking treatment.

[0042] (Lignocellulosic raw material) The lignocellulose raw material is not particularly limited as long as it contains lignocellulose in the structure. For example, pulp raw materials such as wood and non-wood can be mentioned. For example, wood can be coniferous wood such as Yezo spruce, red pine, cedar, and cypress, and broadleaf wood such as white birch and beech. The age of the wood and the part where it is harvested are not important. Therefore, wood harvested from trees of different ages or wood harvested from different parts of a tree may be used in combination. For example, non-wood can be bamboo, kenaf, reed, and rice. The lignocellulose raw material may be one type alone or two or more types in combination. Lignosulfonic acid and lignosulfonates may be prepared from raw materials other than lignocellulose raw materials, for example, lignin. Examples of lignin include naturally occurring lignin and artificially produced lignin (for example, dehydrogenation polymerized products of hydroxycinnamic alcohol analogues), and either can be used. Lignosulfonic acid and lignosulfonates can be prepared from lignin, for example, by a method of decomposing lignin and sulfonating it.

[0043] (sulfurous acid treatment) The sulfite treatment can be carried out by contacting the lignocellulosic raw material with at least one of sulfurous acid and a sulfite salt. The conditions for the sulfite treatment are not particularly limited as long as they allow introduction of a sulfo group to the α-carbon atom of the side chain of lignin contained in the lignocellulosic raw material.

[0044] The sulfite treatment is preferably carried out by sulfite cooking, which allows the lignin in the lignocellulosic raw material to be sulfonated more quantitatively. The sulfite cooking is a method in which the lignocellulosic raw material is reacted at high temperature in a solution of at least one of sulfurous acid and a sulfite salt (e.g., aqueous solution: cooking liquid). This method has been established and is being carried out industrially as a method for producing sulfite pulp, and is therefore advantageous in terms of economy and ease of implementation.

[0045] When sulfite cooking is carried out, examples of the sulfite salt include magnesium salts, calcium salts, sodium salts and ammonium salts.

[0046] The sulfurous acid (SO2) concentration in at least one of the sulfurous acid and sulfite solutions is not particularly limited, but the ratio of mass (g) of SO2 to 100 mL of reaction solution is preferably 1 g / 100 mL or more, and more preferably 2 g / 100 mL or more when sulfite cooking is performed. The upper limit is preferably 20 g / 100 mL or less, and more preferably 15 g / 100 mL or less when sulfite cooking is performed. The SO2 concentration is preferably 1 g / 100 mL to 20 g / 100 mL, and more preferably 2 g / 100 mL to 15 g / 100 mL when sulfite cooking is performed.

[0047] The pH value of the sulfurous acid treatment is not particularly limited, but is usually 10 or less. When sulfurous acid cooking is performed, it is preferably performed under acidic conditions, more preferably pH 5 or less, and even more preferably pH 3 or less. This allows lignin derivatives (e.g., lignin sulfonate) to be efficiently extracted, and pulp of higher quality can be obtained. The lower limit of the pH value is preferably 0.1 or more, and when sulfurous acid cooking is performed, it is more preferably 0.5 or more. The pH value during the sulfurous acid treatment is preferably 0.1 to 10, and when sulfurous acid cooking is performed, it is more preferably 0.5 to 5, and even more preferably 0.5 to 3.

[0048] The temperature of the sulfite treatment is not particularly limited, but is preferably 170° C. or lower, and more preferably 150° C. or lower when sulfite cooking is performed. The lower limit is preferably 70° C. or higher, and more preferably 100° C. or higher when sulfite cooking is performed. The temperature condition of the sulfite treatment is preferably 70 to 170° C., and more preferably 100 to 150° C. when sulfite cooking is performed. The treatment time for the sulfurizing treatment is not particularly limited, and although it depends on the conditions of the sulfurizing treatment, it is preferably 0.5 to 24 hours, more preferably 1.0 to 12 hours.

[0049] In the sulfite treatment, it is preferable to add a compound that supplies a counter cation (salt: containing the substituent M of the group represented by formula (1)). By adding a compound that supplies a counter cation, the pH value in the sulfite treatment can be kept constant. Examples of compounds that supply counter cations include MgO, Mg(OH)2, CaO, Ca(OH)2, CaCO3, NH3, NH4OH, NaOH, NaHCO3, and Na2CO3. The counter cation is preferably a calcium ion, a magnesium ion, or a sodium ion.

[0050] In the sulfurous acid treatment, when a solution of at least one of sulfurous acid and sulfite is used, the solution may contain, in addition to SO2, the above-mentioned counter cation (salt) and a digestion and penetration agent (e.g., a cyclic ketone compound such as anthraquinone sulfonate, anthraquinone, or tetrahydroanthraquinone), as necessary.

[0051] There is no limitation on the equipment used in the sulfite treatment, and for example, generally known dissolving pulp manufacturing equipment can be used.

[0052] The intermediate product may be separated from the solution of at least one of sulfurous acid and sulfite salts by a conventional method, such as a method for separating the sulfurous acid digestion wastewater after the sulfurous acid digestion (e.g., filtration).

[0053] Another example of a method for producing lignosulfonic acid and lignosulfonate salts is a method for sulfonating kraft lignin, which will be described later in this specification. The method for sulfonating kraft lignin may be similar to the method for sulfonation by ordinary sulfite treatment or sulfite cooking treatment, but is not particularly limited and other methods may be used.

[0054] The lignosulfonic acid and lignosulfonate obtained by the sulfite treatment (for example, as the filtrate or filtration residue after filtering the insoluble matter of the sulfite solution, preferably as the filtrate) may be used as the lignin derivative, which is an active ingredient, as it is or after concentrating as necessary. On the other hand, if necessary, other treatments may be further performed. This makes it possible to obtain a lignin derivative having a high purity and / or an appropriate degree of sulfonation (S content). Examples of other treatments include alkali treatment, oxidation treatment, dialysis treatment, and combinations of these.

[0055] (Alkaline treatment) The alkali treatment is preferably carried out on the filtration residue (insoluble matter) or filtrate after the sulfite treatment, or on the treated product after the dialysis treatment. The alkali treatment can be carried out by placing the target sample under alkaline conditions. Placing under alkaline conditions usually means placing the sample in an aqueous solution having a pH value of 8 or more, preferably a pH value of 9 or more. The upper limit of the pH value is usually 14.

[0056] In the alkali treatment, an alkaline substance is usually brought into contact with the sulfite treatment product. The alkaline substance is not particularly limited, but examples thereof include calcium hydroxide, magnesium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia. Among these, sodium hydroxide and calcium hydroxide are preferred. The alkaline substance may be used alone or in combination of two or more.

[0057] Examples of a method for contacting an alkaline substance with the sulfurous acid treated product include a method of preparing a dispersion or solution (e.g., an aqueous dispersion or aqueous solution) of the sulfurous acid treated product and adding an alkaline substance to the dispersion or solution, and a method of adding a solution or dispersion (e.g., an aqueous dispersion or aqueous solution) of the alkaline substance to the sulfurous acid treated product.

[0058] The temperature of the alkali treatment is not particularly limited, but is preferably 40° C. or higher, more preferably 60° C. or higher. The upper limit is preferably 150° C. or lower, more preferably 140° C. or lower, and even more preferably 130° C. or lower.

[0059] The amount of the alkaline substance in the alkali treatment is preferably 0.5 to 40 mass %, more preferably 1.0 to 30 mass %, based on the solids mass of the sulfurous acid treated product, or, when an aqueous solution or dispersion is prepared by dispersing the alkali treated extract in an aqueous solvent (e.g., water), based on the mass of the aqueous solution or dispersion.

[0060] The time for the alkali treatment is not particularly limited, but is preferably 0.1 hours or more, more preferably 0.5 hours or more, and is preferably 10 hours or less, more preferably 6 hours or less.

[0061] Prior to the alkali treatment, the sulfite-treated product may be dissolved, dispersed, or the concentration adjusted (preparation of a solution or dispersion in an aqueous solvent such as water) as necessary. Dispersion can be performed by passing through a disc refiner, adding to a mixer or disperser, kneading, or the like. The concentration can be adjusted, for example, by using an aqueous solvent such as water.

[0062] (Oxidation treatment) The oxidation treatment can be carried out on the treated product obtained after the sulfurous acid treatment (for example, the filtrate after filtration) or the treated product after the alkali treatment. The oxidation treatment can be carried out by using an appropriate oxidizing agent. When the oxidizing agent is a gas, the oxidation treatment can be carried out by bubbling the gas into the filtrate. When the oxidizing agent is a liquid, the oxidation treatment can be carried out by adding the liquid to the filtration residue or the filtrate. The oxidizing agent is preferably air, oxygen, hydrogen peroxide, ozone, or a combination thereof. The oxidation treatment is preferably carried out under alkaline conditions (alkaline oxidation treatment). The treatment pH of the alkaline oxidation treatment is usually 8 or more, preferably 10 or more, and more preferably 12 or more. The temperature of the oxidation treatment is usually 20 to 200°C, and preferably 50 to 180°C. The time of the oxidation treatment is usually preferably 0.1 hours or more, and more preferably 0.5 hours or more. The upper limit is preferably 5 hours or less, and more preferably 3 hours or less.

[0063] (Dialysis or UF treatment) The dialysis treatment can be performed on the treated product obtained after the sulfite treatment (for example, the filtrate after filtration). Examples of the dialysis membrane include cellulose-based membranes such as cellulose acetate, and synthetic polymer-based membranes such as ethylene vinyl alcohol, polyacrylonitrile, polymethyl methacrylate, polysulfone, and polyethersulfone, and the molecular weight fraction is usually 5,000 to 100,000, preferably 7,000 to 80,000, and more preferably 10,000 to 50,000.

[0064] Instead of dialysis, UF treatment can be used. As the UF membrane, a known UF membrane can be used. For example, a hollow fiber membrane, a spiral membrane, a tubular membrane, and a flat membrane can be used. As the material of the UF membrane, a known material can be used. For example, cellulose acetate, aromatic polyamide, polyvinyl alcohol, polysulfone, polyvinylidene fluoride, polyethylene, polyacrylonitrile, and ceramic can be used. The UF membrane may be a commercially available product.

[0065] The molecular weight cutoff of the UF membrane is preferably 5,000 to 30,000, more preferably 10,000 to 25,000, and even more preferably 15,000 to 23,000. When a UF membrane with a molecular weight cutoff of 5,000 or more is used, it is possible to prevent the separation speed of the treatment liquid from being excessively slowed. In addition, when a UF membrane with a molecular weight cutoff of 30,000 or less is used, it is possible to prevent lignin from being unable to be separated from the treatment liquid.

[0066] The concentration ratio by the UF treatment using the UF membrane can be set arbitrarily. In other words, the UF treatment can be stopped when the outflow amount of the concentrated liquid reaches an arbitrary amount. It is preferable to concentrate 2 to 6 times. Concentrating 2 to 6 times means that the amount of the raw liquid (black liquor) becomes 1 / 2 to 1 / 6.

[0067] The temperature of the treatment liquid during UF treatment is not particularly limited. For example, it is preferably 20 to 80°C, and more preferably 20 to 70°C in consideration of the heat resistance of the UF membrane material. The pH value of the treatment liquid during UF treatment is preferably 2 to 11. The solid content concentration (w / w) of the black liquor during UF treatment is preferably 2 to 30%, more preferably 5 to 20%.

[0068] (Kraft lignin) Kraft lignin is also called thiolignin or sulfate lignin. Kraft lignin can be obtained, for example, by adding an acid to black liquor obtained by kraft cooking of lignocellulosic raw materials and then precipitating the black liquor.

[0069] Kraft cooking can be carried out by placing wood chips, which are lignocellulose raw materials, in a pressure-resistant vessel together with a kraft cooking liquor containing caustic soda (NaOH) and sodium sulfide (Na2S). The liquid ratio of wood chips to cooking liquor can be, for example, 1.0 to 40 L / kg, preferably 1.5 to 30 L / kg, and more preferably 2.0 to 30 L / kg. In another embodiment, the liquid ratio of wood chips to chemical liquor can be, for example, 1.0 to 5.0 L / kg, preferably 1.5 to 4.5 L / kg, and more preferably 2.0 to 4.0 L / kg.

[0070] In the present invention, in addition to caustic soda (NaOH) and sodium sulfide (Na2S), various cooking aids can also be used in combination in the kraft cooking. For example, an alkaline cooking liquor containing 0.01 to 5% by mass of a quinone compound per bone-dry chips may be added to the digester.

[0071] The quinone compound used is a quinone compound, a hydroquinone compound, or a precursor thereof as a so-called known cooking aid, and at least one compound selected from these can be used. Examples of these compounds include anthraquinone, dihydroanthraquinone (e.g., 1,4-dihydroanthraquinone), tetrahydroanthraquinone (e.g., 1,4,4a,9a-tetrahydroanthraquinone, 1,2,3,4-tetrahydroanthraquinone), methylanthraquinone (e.g., 1-methylanthraquinone, 2-methylanthraquinone), methyldihydroanthraquinone (e.g., 2-methyl-1,4-dihydroanthraquinone), methyltetrahydroanthraquinone (e.g., 1-methyl-1,4,4a,9a-tetrahydroanthraquinone, 2 ... quinone compounds such as anthrahydroquinone (generally 9,10-dihydroxyanthracene), methylanthrahydroquinone (e.g., 2-methylanthrahydroquinone), dihydroanthrahydroanthraquinone (e.g., 1,4-dihydro-9,10-dihydroxyanthracene) or an alkali metal salt thereof (e.g., disodium salt of anthrahydroquinone, disodium salt of 1,4-dihydro-9,10-dihydroxyanthracene), and precursors such as anthrone, anthranol, methylanthrone, and methylanthranol. These precursors have the potential to be converted into quinone compounds or hydroquinone compounds under cooking conditions.

[0072] The cooking liquor may have an active alkali addition rate (AA) of 8 to 55% by mass, preferably 8 to 20% by mass, based on the absolute dry wood chip mass. If the active alkali addition rate is less than 8% by mass, the removal of lignin and hemylulose becomes insufficient, and if it exceeds 55% by mass, the yield and quality decrease. Here, the active alkali addition rate is the addition rate of NaOH and Na2S converted into the addition rate of Na2O, and can be converted into the addition rate of Na2O by multiplying the addition rate of NaOH by 0.775. In addition, the sulfidity is preferably in the range of 15 to 40%. In the region of a sulfidity of less than 15%, it leads to a decrease in delignification property, a decrease in pulp viscosity, and an increase in the lees rate.

[0073] Kraft cooking is preferably carried out at a temperature range of 120 to 180°C, more preferably 140 to 160°C. If the temperature is too low, delignification (reduction in kappa number) is insufficient, while if the temperature is too high, the degree of polymerization (viscosity) of cellulose decreases. The cooking time in the present invention is the time from when the cooking temperature reaches the maximum temperature to when the temperature starts to decrease, and the cooking time is preferably 60 minutes or more and 600 minutes or less, more preferably 120 minutes or more and 360 minutes or less. If the cooking time is less than 60 minutes, pulping does not proceed, and if it exceeds 600 minutes, pulp production efficiency is deteriorated, which is not preferable.

[0074] After the kraft cooking, filtration is performed, and the resulting alkaline black liquor (filtrate) is precipitated with an acid to prepare acid-precipitated kraft lignin. Examples of this method include methods for preparing powdered acid-precipitated kraft lignin (WO 2006 / 038863, WO 2006 / 031175, WO 2012 / 005677).

[0075] In addition, for example, kraft lignin can be obtained by passing carbon dioxide through the obtained alkaline black liquor to lower the pH of the black liquor to about 10, separating the precipitated lignin particles by filtration, resuspending the separated lignin particles, adding sulfuric acid to lower the pH to about 2, separating the obtained precipitate by filtration, and further washing and drying the precipitate, etc.

[0076] (Soda lignin) Soda lignin can be obtained by precipitating black liquor obtained by soda cooking of lignocellulosic raw materials by adding an acid or the like to the black liquor.

[0077] Soda cooking can be carried out by placing wood chips, which are lignocellulose raw materials, in a pressure-resistant vessel together with soda cooking liquor (aqueous sodium hydroxide solution). The liquid ratio of wood chips to cooking liquor can be, for example, 1.0 to 40 L / kg, preferably 1.5 to 30 L / kg, and more preferably 2.0 to 30 L / kg. In another embodiment, the liquid ratio of wood chips to cooking liquor can be, for example, 1.0 to 5.0 L / kg, preferably 1.5 to 4.5 L / kg, and more preferably 2.0 to 4.0 L / kg.

[0078] In the present invention, in addition to caustic soda (NaOH), various cooking aids can also be used in soda cooking. For example, it is preferable to add an alkaline cooking liquor containing 0.01 to 5 mass% of a quinone compound per bone-dry chip to the digester. If the amount of the quinone compound added is less than 0.01 mass%, the effect of the aid cannot be fully exerted, and even if the amount of the quinone compound added exceeds 5 mass%, the aid remains significantly in the pulp, affecting the quality and safety when paper is produced from the pulp. The quinone compound can be the same as that described in the kraft cooking.

[0079] The cooking liquor may have a caustic soda addition rate of 1 to 50% by mass, preferably 10 to 30% by mass, based on the mass of bone dry wood chips. If the addition rate is less than 1% by mass, the removal of lignin and hemylulose becomes insufficient, and if it exceeds 50% by mass, a decrease in yield and a decrease in quality occur.

[0080] The soda cooking is preferably carried out at a temperature range of 120 to 180°C, more preferably 140 to 160°C. If the temperature is too low, delignification (reduction in kappa number) is insufficient, while if the temperature is too high, the degree of polymerization (viscosity) of cellulose decreases. The cooking time in the present invention is the time from when the cooking temperature reaches the maximum temperature to when the temperature starts to decrease, and the cooking time is preferably 60 minutes or more and 600 minutes or less, more preferably 120 minutes or more and 360 minutes or less. If the cooking time is less than 60 minutes, pulping does not proceed, and if it exceeds 600 minutes, pulp production efficiency is deteriorated, which is not preferable.

[0081] After soda cooking, filtration is performed, and the resulting alkaline black liquor (filtrate) is precipitated with acid to produce acid-precipitated soda lignin. For example, sulfuric acid is added to the alkaline black liquor to lower the pH to about 2, and the resulting precipitate is separated by filtration, and the precipitate is further washed with water and dried to obtain soda lignin.

[0082] The kraft lignin and soda lignin obtained as described above may be further purified as necessary to be used as a lignin derivative having a higher purity. In addition, other treatments may be further performed as necessary. The derivatization of lignin is not particularly limited, and may be, for example, sulfomethylation.

[0083] (Sulfomethylated lignin) Kraft lignin, soda lignin, soda-anthraquinone lignin, organosolv lignin, explosive lignin, lignin sulfonate, sulfate lignin, etc., preferably kraft lignin and soda lignin, more preferably kraft lignin, can be derivatized by introducing a sulfo group into the aromatic nucleus via carbon by sulfomethylation and used as sulfomethylated lignin.

[0084] In the sulfomethylation reaction of kraft lignin, a sulfo group is generally introduced to the aromatic nucleus via carbon at the position shown in the following general formula (1) for the C6-C3 unit of lignin. General formula (1) shows the C6-C3 unit, which is a partial structure of lignin. That is, in the reaction indicated by the arrow on the left, a sulfo group is introduced at the α-position, and this is generally called sulfonation. On the other hand, in the reaction indicated by the arrow on the right, a sulfo group is introduced at the 5-position of the aromatic nucleus via formaldehyde in addition to the α-position.

[0085] [ka] (In the general formula (1), M represents a hydrogen atom, a monovalent metal, or a divalent metal.)

[0086] The sulfomethylated lignin may be produced by a known method, for example, by reacting kraft lignin or soda lignin with a sulfite and an aldehyde.

[0087] An example of a method for sulfomethylating lignin is disclosed in U.S. Patent No. 2,680,113. In this method, the sulfomethylation reaction of lignin is carried out at a temperature range of 50 to 200° C., preferably at a temperature range of 80 to 170° C., and more preferably at a temperature range of 90 to 160° C. In addition, the pH during the sulfomethylation reaction is preferably 8 or higher.

[0088] The amount of sulfite to be added is preferably 1 to 50% by mass based on lignin, from the viewpoints of efficiently carrying out the reaction and preventing unreacted substances from remaining when an excessive amount of sulfite is added.

[0089] As the aldehyde, formaldehyde is preferable. The amount of aldehyde to be added is preferably 0.25 to 12.5% ​​by mass based on lignin. When the amount of formaldehyde is within this range, the reaction indicated by the arrow on the right side of the above general formula (1) proceeds smoothly, and a sulfo group is introduced via formaldehyde.

[0090] (optional ingredient) The lignin component may contain components other than the extracted components that are mixed in from the raw material when the lignin derivative is prepared (e.g., during sulfite cooking), such as inorganic salts such as sodium sulfate, sodium sulfite, sodium chloride, magnesium sulfate, magnesium sulfite, magnesium chloride, calcium sulfate, calcium sulfite, calcium chloride, ammonium sulfate, ammonium sulfite, ammonium chloride, and sodium hydroxide.

[0091] In the negative electrode composition of the present invention, the ratio of the silicon-based negative electrode active material and the dispersant is preferably 0.1 to 5 parts by mass, more preferably 0.3 to 4.5 parts by mass, and even more preferably 0.5 to 4 parts by mass, based on the solid content, per 100 parts by mass of the silicon-based negative electrode active material, from the viewpoint of adding a necessary and sufficient amount of dispersant for dispersing the silicon-based negative electrode active material. In addition, the negative electrode composition of the present invention may be used as a negative electrode composition in a state of being dispersed in a dispersion medium, so long as it contains a silicon-based negative electrode active material and a dispersant.

[0092] (Negative electrode) The negative electrode of the present invention is used in a secondary battery, and includes a negative electrode active material layer containing the negative electrode composition of the present invention, a negative electrode binder, and a conductive assistant.

[0093] The content of the negative electrode composition in the negative electrode active material layer is preferably from 10 to 99 mass %, more preferably from 90 to 99 mass %, based on the solid content.

[0094] The content of the silicon-based negative electrode active material in the negative electrode active material layer is preferably 1 to 99 mass%, more preferably 10 to 99 mass%, further preferably 50 to 99 mass%, particularly preferably 60 to 99 mass%, and most preferably 65 to 99 mass%, based on the solid content.

[0095] When a silicon-based negative electrode active material is used in combination with another negative electrode active material, the total content of the negative electrode active materials in the negative electrode active material layer is preferably 90 to 99 mass%, more preferably 91 to 99 mass%, even more preferably 92 to 99 mass%, still more preferably 95 to 99 mass%, particularly preferably 96 to 99 mass%, and most preferably 98 to 99 mass%, based on the solid content.

[0096] The content of the dispersant in the negative electrode active material layer is preferably from 0.05 to 10 mass %, more preferably from 0.1 to 5 mass %, based on the solid content.

[0097] (Negative electrode binder) The negative electrode binder used in the present invention is not particularly limited as long as it is a binder generally used for negative electrodes, but it is preferable to use carboxymethylcellulose or a salt thereof from the viewpoint of high performance when preparing a negative electrode in a water system. In addition, the negative electrode binder may contain other binders other than carboxymethylcellulose or a salt thereof. Examples of other binders include synthetic rubber binders.

[0098] (Carboxymethylcellulose and / or its salts) Carboxymethylcellulose and / or its salt (hereinafter sometimes abbreviated as "CMC") has a structure in which the hydroxyl group in the glucose unit constituting cellulose is replaced with a carboxymethyl ether group. Carboxymethylcellulose may be in the form of a salt. Examples of the salt of carboxymethylcellulose include metal salts such as sodium carboxymethylcellulose.

[0099] In the present invention, cellulose refers to a polysaccharide having a structure in which D-glucopyranose (also simply called "glucose unit" or "anhydroglucose") is linked together through β,1-4 bonds. Cellulose is generally classified into natural cellulose, regenerated cellulose, fine cellulose, microcrystalline cellulose excluding the amorphous region, etc., based on the origin, manufacturing method, etc.

[0100] Examples of natural cellulose include bleached or unbleached pulp, refined linters, and cellulose produced by microorganisms such as acetic acid bacteria. The raw material for bleached or unbleached pulp is not particularly limited, and examples thereof include wood, cotton, straw, bamboo, and the like. The method for producing bleached or unbleached pulp is also not particularly limited, and examples thereof include mechanical methods, chemical methods, and methods that combine mechanical and chemical methods. Examples of bleached or unbleached pulp include mechanical pulp, chemical pulp, groundwood pulp, sulfite pulp, kraft pulp, and pulp for papermaking. Examples of bleached or unbleached pulp also include dissolving pulp, which is chemically refined and mainly dissolved in chemicals for use, and is the main raw material for artificial fibers, cellophane, and the like.

[0101] An example of regenerated cellulose is regenerated cellulose obtained by dissolving cellulose in a solvent such as a cuprammonium solution, a cellulose xanthate solution, or a morpholine derivative, and then spinning the solution again.

[0102] Examples of fine cellulose include fine cellulose obtained by depolymerizing cellulosic materials such as natural cellulose and regenerated cellulose through acid hydrolysis, alkali hydrolysis, enzymatic decomposition, crushing treatment, vibrating ball mill treatment, etc., and fine cellulose obtained by mechanically treating cellulosic materials.

[0103] For producing CMC, a known CMC production method can be applied. For example, cellulose is treated with a mercerizing agent (alkali) to prepare mercerized cellulose (alkali cellulose), and then an etherifying agent is added to the mercerized cellulose to perform an etherification reaction, thereby producing CMC.

[0104] The cellulose raw material can be any of the above-mentioned cellulose raw materials without any particular limitations, but cellulose with high purity is preferred, and dissolving pulp or linter is more preferred. By using these, CMC with high purity can be obtained.

[0105] Examples of the mercerizing agent include alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, etc. Examples of the etherifying agent include monochloroacetic acid, sodium monochloroacetate, etc.

[0106] In a general method for producing water-soluble carboxymethylcellulose, the molar ratio of the mercerizing agent to the etherifying agent (mercerizing agent / etherifying agent) is generally 2.00 to 2.45 when monochloroacetic acid is used as the etherifying agent. The reason is that when the molar ratio is 2.00 or more, the etherification reaction can be sufficiently carried out, and the unreacted monochloroacetic acid can be prevented from being wasted. When the molar ratio is 2.45 or less, the side reaction caused by the excess mercerizing agent and monochloroacetic acid can be prevented from progressing to produce an alkali metal glycolate, which is economical. In the present invention, the CMC may be a commercially available product, for example, a product name "Sunrose" manufactured by Nippon Paper Industries Co., Ltd.

[0107] (Degree of substitution of carboxymethyl group) The CMC has a degree of substitution of carboxymethyl groups per anhydrous glucose unit (hereinafter sometimes referred to as DS value) of 0.5 to 1.2. By having a DS value of 0.5 or more, it is possible to maintain good solubility in water and suppress the generation of undissolved matter. Furthermore, by having a DS value of 1.2 or less, it is possible to suppress an increase in spinnability of the liquid and maintain easy handling. Therefore, the DS value of the CMC of the present invention is 0.5 to 1.2, preferably 0.5 to 1.0, and more preferably 0.6 to 1.0.

[0108] The degree of substitution of the carboxymethyl group is measured as follows. Weigh out approximately 2.0 g of sample and place it in a 300 mL Erlenmeyer flask with a stopper. Add 100 mL of a solution of 100 mL of concentrated nitric acid in 1000 mL of methanol, and shake for 3 hours to convert carboxymethylcellulose salt (CMC) to H-CMC (hydrogen-type carboxymethylcellulose). Weigh out 1.5 to 2.0 g of the bone-dry H-CMC and place it in a 300 mL Erlenmeyer flask with a stopper. Moisten the H-CMC with 15 mL of 80% methanol, add 100 mL of 0.1 N-NaOH, and shake for 3 hours at room temperature. Using phenolphthalein as an indicator, back-titrate the excess NaOH with 0.1 N-H2SO4, and calculate the degree of carboxymethyl substitution (DS value) using the following formula. A = [(100 × F'-0.1N-H2SO4 (mL) × F) × 0.1] / (bone dry mass of H-CMC (g)) Degree of carboxymethyl substitution = 0.162 x A / (1-0.058 x A) F': Factor of 0.1N-H2SO4 F: Factor of 0.1N-NaOH

[0109] (viscosity) The viscosity of a 1% by mass aqueous solution of CMC measured at 25° C. using a Brookfield viscometer (30 rpm) is preferably 1,000 to 20,000 mPa·s, more preferably 1,000 to 15,000 mPa·s, and even more preferably 1,000 to 10,000 mPa·s. If the viscosity is too high, there are problems such as the inability to mix well with the active material and conductive assistant when preparing the slurry, and the problem that the slurry has poor fluidity when applied to the current collector and cannot be applied, while if the viscosity is too low, there are problems such as the slurry flowing off the current collector when applied to the current collector and therefore cannot be applied well, and the possibility of migration of the active material occurring after application.

[0110] The viscosity was measured by the following method. CMC is weighed into a 1000 mL glass beaker and dispersed in 900 mL of distilled water to prepare an aqueous dispersion with a solid content of 1% (w / v). The aqueous dispersion is stirred at 600 rpm for 3 hours at 25°C using a stirrer. The viscosity is then measured after 3 minutes at 30 rpm using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd.) according to the method of JIS-Z-8803.

[0111] The CMC may be one type, or a combination of two or more types of CMC with different DS values, viscosities, molecular weights, etc.

[0112] (Synthetic rubber binder) As the synthetic rubber binder, one or more selected from the group consisting of styrene butadiene rubber (SBR), nitrile butadiene rubber, methyl methacrylate butadiene rubber, chloroprene rubber, carboxy-modified styrene butadiene rubber, and latexes of these synthetic rubbers can be used. Among these, styrene butadiene rubber (SBR) is preferred.

[0113] Here, the average particle size (D50) of the SBR is preferably 50 to 300 nm, and more preferably 50 to 200 nm. If the average particle size (D50) of the SBR is too large, the SBR does not adhere uniformly to the active material, reducing the binder function and causing a problem of high electrical resistance, whereas if it is too small, the SBR covers the active material, causing a problem of high electrical resistance.

[0114] The glass transition temperature (Tg) of SBR is preferably −50° C. to 50° C. When the glass transition temperature (Tg) is within the above range, the SBR is well mixed with the carboxymethyl cellulose and / or a salt thereof contained in the negative electrode mixture composition and the negative electrode composition of the present invention, and has appropriate flexibility when used in a negative electrode layer, so that the electrical resistance is unlikely to become high.

[0115] When CMC and SBR are used in combination as the negative electrode binder, it is preferable to use 50 to 500 parts by mass of SBR per 100 parts by mass of CMC on a solids basis, from the viewpoint of obtaining optimal binder performance.

[0116] The content ratio of the negative electrode binder in the negative electrode active material layer and the dispersant contained in the negative electrode composition is preferably 1 to 100 parts by mass, and more preferably 2 to 50 parts by mass, of the dispersant per 100 parts by mass of the negative electrode binder, based on the solid content, from the viewpoint of containing each in a balanced amount necessary and sufficient to exhibit its effect.

[0117] (Conductive assistant) The negative electrode active material layer contains a conductive assistant. Examples of the conductive assistant include conductive carbon such as carbon black, acetylene black, and ketjen black. The content of the conductive assistant in the negative electrode active material layer is usually 0.01 to 20 mass %, preferably 0.1 to 10 mass %, based on the solid content.

[0118] (Method of manufacturing negative electrode) The negative electrode of the present invention can be obtained, for example, by preparing a slurry-like negative electrode mixture composition containing the negative electrode composition of the present invention, a negative electrode binder, a conductive auxiliary, and other auxiliary agents used as necessary, and a solvent, and then coating and drying the slurry on a current collector, thereby forming a negative electrode in which a negative electrode active material layer is formed on a current collector.

[0119] The method for producing the negative electrode mixture composition is not particularly limited. For example, the negative electrode composition of the present invention and the negative electrode binder are dissolved or dispersed in a solvent, and other materials used in the negative electrode mixture composition are added thereto, and mixed while stirring as necessary. In addition, a method may be adopted in which the negative electrode composition of the present invention, the negative electrode binder, the conductive assistant, and other assistants used as necessary are mixed in advance, a solvent is added thereto, and the mixture is mixed while stirring as necessary. In addition, the properties of the negative electrode mixture composition are not particularly limited. For example, liquid, paste, slurry, etc. may be mentioned, and any of them may be used.

[0120] The solvent used in the negative electrode mixture composition is preferably an aqueous solvent. The type of aqueous solvent is not particularly limited, but is preferably water, a water-soluble organic solvent, or a mixed solvent thereof, and more preferably water.

[0121] The water-soluble organic solvent is an organic solvent that dissolves in water. Examples of the water-soluble organic solvent include methanol, ethanol, 2-propanol, butanol, glycerin, acetone, methyl ethyl ketone, 1,4-dioxane, N-methyl-2-pyrrolidone, tetrahydrofuran (THF), N,N-dimethylformamide (DMF), N,N-dimethylacetamide, dimethyl sulfoxide (DMSO), acetonitrile, methyl triglycol succinate, acetic acid, and combinations thereof.

[0122] When the mixed solvent is used as the aqueous solvent, the amount of the water-soluble organic solvent in the mixed solvent is preferably 10% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more. The upper limit of the amount is not limited, but is preferably 95% by mass or less, and more preferably 90% by mass or less. In addition, the aqueous solvent may contain a non-water-soluble organic solvent within a range that does not impair the effects of the invention.

[0123] Examples of the method for applying the negative electrode mixture composition on the current collector include blade coating, bar coating, and die coating, and blade coating is preferred. For example, in the case of blade coating, a method of casting the negative electrode mixture composition on the current collector using a coating device such as a doctor blade is exemplified. In addition, the coating method is not limited to the above specific example, and a method of discharging the negative electrode mixture composition from an extrusion type injector having a slot nozzle onto the current collector wound around a backup roll and running is also exemplified. In blade coating, after casting, if necessary, drying by heating (temperature is, for example, 80 to 120°C, heating time is, for example, 4 to 12 hours) or pressing by roll press or the like is performed to obtain a negative electrode active material layer.

[0124] The shape of the electrode is not particularly limited, but is usually a sheet. The thickness of the sheet-shaped electrode plate (thickness of the negative electrode active material layer formed from the negative electrode mixture composition, excluding the current collector portion) is difficult to specify because it depends on the composition and manufacturing conditions of the composition, but is usually 30 to 150 μm.

[0125] (Anode current collector) The current collector may be any electrical conductor that will not cause a fatal chemical reaction in the electrode or battery.

[0126] Examples of materials for the negative electrode current collector include stainless steel, nickel, copper, titanium, carbon, copper or stainless steel having carbon, nickel, titanium or silver attached thereto, etc. Among these, copper or a copper alloy is preferred, and copper is more preferred. The shape of the current collector can be, for example, a mesh, a punched metal, a foam metal, or a foil processed into a plate shape, with a foil processed into a plate shape being preferred.

[0127] (Lithium-ion battery) The secondary battery including the above-mentioned negative electrode of the present invention is preferably a lithium ion battery (lithium ion secondary battery). The lithium ion secondary battery may have a structure in which positive electrodes and negative electrodes are alternately stacked with separators interposed therebetween and wound many times. The stack of the positive electrodes, separators, and negative electrodes wound many times is placed in a battery container, and a non-aqueous electrolyte is injected and sealed to obtain a lithium ion secondary battery.

[0128] (positive electrode) The positive electrode has, for example, a positive electrode active material layer on a positive electrode current collector.

[0129] The positive electrode active material layer contains one or more positive electrode active materials capable of absorbing and releasing lithium ions, and may contain other materials such as a positive electrode binder, a positive electrode conductive assistant, and a dispersant as necessary. In this case, details regarding the positive electrode binder and the positive electrode conductive assistant are the same as those of the negative electrode binder and the negative electrode conductive assistant already described. Examples of the positive electrode binder include carboxymethylcellulose and / or its salt, synthetic rubber binders, and polytetrafluoroethylene (PTFE), which are listed as the negative electrode binders.

[0130] (Cathode active material) The positive electrode active material is LiFePO4, LiMe x O y (Me represents a transition metal including at least one of Ni, Co, and Mn; x and y represent arbitrary numbers)-based positive electrode active materials are preferred.

[0131] (Positive electrode current collector) Examples of materials for the positive electrode current collector include metals such as aluminum and stainless steel, with aluminum being preferred.

[0132] (Separator) The separator may be, for example, a microporous membrane or a nonwoven fabric made of a polyolefin such as polyethylene or polypropylene, and may be impregnated with a nonaqueous electrolyte.

[0133] (Non-aqueous electrolyte) The non-aqueous electrolyte usually contains a lithium salt and a non-aqueous solvent. Examples of the lithium salt include LiPF6, LiAsF6, LiBF4, and LiClO4. Examples of the non-aqueous solvent include ethylene carbonate, diethyl carbonate, dimethyl carbonate, propylene carbonate, butylene carbonate, and methyl ethyl carbonate. The non-aqueous solvent may be used alone or in combination of two or more. The concentration of the lithium salt in the non-aqueous electrolyte is usually 0.5 to 2.5 mol / L.

[0134] The shape of the lithium ion secondary battery is not particularly limited, and may be a cylindrical type, a square type, a flat type, a coin type, a button type, a sheet type, etc. The material of the battery container is not particularly limited as long as it can prevent moisture from entering the battery, and examples of the material include metal, laminate of aluminum, etc.

[0135] The negative electrode composition of the present invention contains a lignin component containing a specific lignin derivative, and therefore has excellent dispersibility of silicon-based negative electrode active material. In the negative electrode obtained by adding this negative electrode composition, the silicon-based negative electrode active material is uniformly dispersed, forming an effective conductive path. Therefore, the lithium ion battery using the negative electrode of the present invention is suppressed from irreversible capacity loss due to electrical disconnection caused by volume change of the negative electrode active material during charge / discharge cycles, and as a result, has excellent battery performance such as capacity retention rate. EXAMPLES

[0136] Hereinafter, the present invention will be described in detail with reference to examples, but the present invention is not limited thereto.

[0137] <Measurement and evaluation methods> In the examples, comparative examples and reference examples, measurements and evaluations were carried out as follows.

[0138] (Average particle size of SiOx) In the examples and comparative examples, the average particle size of SiOx in the SiOx dispersion obtained in the active material dispersibility tests 1 and 2 was measured using a Zetasizer 3000HSA (manufactured by Malvern). The measurement sample was prepared by adding 2 mL of water to a 4.5 mL polystyrene cuvette, adding 20 μL of the SiOx dispersion, and diluting by gently stirring.

[0139] (Methoxy group amount) The amount of methoxy groups in the lignin derivatives produced in each production example was measured by the Viebock and Schwappach method for quantitative determination of methoxy groups (see "Lignin Chemical Research Methods", pp. 336-340, 1994, published by Uni Publishing Co., Ltd.).

[0140] (Amount of extracted components) The amount of extractable components was measured by the measurement method for hexane extractable substances described in JIS K 0102:2019.

[0141] (S content) The S content of the sulfo group (-SO3M) of the lignin derivative produced in each production example was calculated by the following formula. S content (mass%) = total S content (mass%) - inorganic S content (mass%) (The S content in the formula indicates the S content relative to the solid content of the lignin sample.) In the formula, the total S content was determined by ICP atomic emission spectrometry, and the inorganic S content was calculated using the sum of the SO3 ion content, SO4 ion content, and S2O3 ion content determined by ion chromatography.

[0142] (Total decomposition product yield by alkaline nitrobenzene oxidation) The total decomposition product yield by alkaline nitrobenzene oxidation of the lignin derivatives produced in each production example was measured by the method described in "Plant Cell Wall Experimental Method" (see "Plant Cell Wall Experimental Method", pp. 128-131, 2016, Hirosaki University Press). The total decomposition product yield was calculated as the ratio (w / w%) of the total weight of the six decomposition products (p-hydroxybenzaldehyde, p-hydroxybenzoic acid, vanillin, vanillic acid, syringaldehyde, and syringic acid) obtained in the measurement to the solid content of the sample.

[0143] (Weight average molecular weight, polydispersity) The weight average molecular weight and polydispersity of the lignin derivatives produced in each production example were measured / calculated by the methods described in the specification.

[0144] (Discharge capacity (charge / discharge rate test)) The charge and discharge rate test of the coin-type lithium-ion secondary batteries produced in the Examples and Comparative Examples was carried out using Nagano Corporation's BTS2004 in a thermostatic chamber at 25° C., with 52 cycles being performed, with one cycle being a charge and discharge cycle in that order, using the coin-type lithium-ion secondary batteries. Note that the charging conditions were constant current constant voltage (CC-CV) (CC current 0.2C, CV voltage 4.2V, final current 0.02C) for all cycles. As a condition for the discharge treatment, the final voltage was set to 3.0 V. In the first cycle, the discharge treatment was performed at a constant current of 0.2 C, and the discharge capacity (mAh / g) after one cycle was measured. After that, up to the 52nd cycle, the constant current for the discharge treatment was set as follows, and the discharge capacity (mAh / g) was measured after each cycle of discharge. (Constant current for discharge treatment in each cycle) 2 to 10 cycles: Discharge treatment at a constant current of 0.2C 11 to 20 cycles: constant current 1C for discharge treatment 21 cycles: Discharge treatment at constant current of 0.2C 22 to 31 cycles: constant current 2C for discharge treatment 32 cycles: Discharge treatment at constant current of 0.2C 33-42 cycles: constant current 3C for discharge treatment 43~52 cycles: constant current 0.2C for discharge treatment

[0145] (Capacity maintenance rate) The capacity retention rate was calculated from the discharge capacity (mAh / g) in each cycle test described above using the formula: "Capacity retention rate = discharge capacity after 52 cycles (mAh / g) / discharge capacity after 1 cycle (mAh / g) × 100." The results are shown in Table 2.

[0146] (Production Example 1) (Production of highly modified lignin derivative A) Wood chips (radiata pine) were subjected to sulfite treatment based on the sulfite cooking method. In the sulfite treatment, a solution of sodium sulfite with a SO2 concentration of 4 g / 100 mL was used, and the temperature was 140°C, pH was 2, and the treatment time was 4 hours. Next, the intermediate composition was filtered and dehydrated to obtain filtrate 1 and pulp (sulfite-treated product). Next, the pulp was suspended in 5% by mass of NaOH (relative to pulp solids) and then subjected to an alkali treatment, and then filtered to separate the alkali-treated pulp and the alkali-treated extract, and alkali-treated extract 1 was obtained as a filtrate. The alkali treatment was performed under the conditions of contacting with 5% by mass of NaOH (relative to pulp solids) and treating at 100°C for 2 hours.

[0147] The obtained filtrate 1 and the alkali-treated extract 1 were mixed in a solid content mass ratio of 9 / 1 (filtrate 1 / alkali-treated extract 1), to obtain raw material 1. The obtained raw material 1 was concentrated in a rotary evaporator until the solid content was 50%. The pH of the solution was then adjusted to pH 4.5 with NaOH, and powdered with a spray dryer. The obtained powder was dissolved in water to prepare an aqueous solution with a solid content of 25%, and the pH was adjusted to 13 with 40% NaOH, and then the solution was subjected to alkaline air oxidation at 160°C for 120 minutes. Then, 70% sulfuric acid was added to adjust the pH to 3, and the precipitate was separated and precipitated. The obtained precipitate was washed with water until the filtrate became neutral, and 20 parts of the precipitate was suspended in 80 parts of water, and the precipitate was completely dissolved by adding 40% NaOH with stirring after heating to 60°C until the pH became 9. The resulting solution was powdered using a spray dryer to obtain highly modified lignin derivative A (methoxy group content: 11.9 mass%, extractable component content: 0.7 mass%, extractable component content / methoxy group content: 0.06, S content of sulfo groups: 1.6 mass%, total decomposition product yield by nitrobenzene oxidation: 7.1%).

[0148] (Production Example 2) (Production of highly modified lignin derivative B) Wood chips (radiata pine) were subjected to sulfite treatment based on the sulfite cooking method. In the sulfite treatment, a solution of sodium sulfite with a SO2 concentration of 2.5 g / 100 mL was used, and the temperature was 140°C, pH was 3, and the treatment time was 4 hours. Next, the intermediate composition was filtered and dehydrated to obtain filtrate 2 and pulp (sulfite-treated product). Next, the pulp was suspended in 5% by mass of NaOH (relative to pulp solids) and then subjected to an alkali treatment, and then filtered to separate the alkali-treated pulp and the alkali-treated extract, and alkali-treated extract 2 was obtained as a filtrate. The alkali treatment was performed under the conditions of contacting with 5% by mass of NaOH (relative to pulp solids) and treating at 100°C for 2 hours.

[0149] The obtained filtrate 2 and the alkali-treated extract 2 were mixed in a solid content mass ratio of 9 / 1 (filtrate 2 / alkali-treated extract 2), to obtain raw material 2. The obtained raw material 2 was concentrated in a rotary evaporator until the solid content was 50%. The pH of the solution was then adjusted to pH 4.5 with NaOH, and powdered with a spray dryer. The obtained powder was dissolved in water to prepare an aqueous solution with a solid content of 25%, and the pH was adjusted to 12 with 40% NaOH, and then the solution was subjected to alkaline air oxidation at 150°C for 120 minutes. Then, 70% sulfuric acid was added to adjust the pH to 3, and the precipitate was separated and precipitated. The obtained precipitate was washed with water until the filtrate became neutral, and 20 parts of the precipitate was suspended in 80 parts of water, and the precipitate was completely dissolved by adding 40% NaOH with stirring after heating to 60°C until the pH became 9. The obtained solution was powdered using a spray dryer to obtain highly modified lignin derivative B (methoxy group content: 11.8% by mass, extractable component content: 1.1% by mass, extractable component content / methoxy group content: 0.10, S content of sulfo groups: 2.7% by mass, total decomposition product yield by nitrobenzene oxidation: 8.9%).

[0150] (Production Example 3) (Production of highly modified lignin derivative C) Raw material 1 containing alkali-treated extract 1 prepared in Production Example 1 was concentrated in a rotary evaporator until the solid content was 50%. The pH of the solution was then adjusted to pH 4.5 with NaOH, and powdered with a spray dryer. The obtained powder was dissolved in water to prepare an aqueous solution with a solid content of 25%, and dialyzed for 3 days using a dialysis membrane (molecular weight cutoff: 20,000, Spectra / Pore cellulose ester dialysis tube). The solution in the dialysis tube was collected, concentrated until the original solution volume was 25%, and powdered with a spray dryer to obtain dialyzed product 1. Into a 3 L autoclave equipped with a stirrer and a temperature controller, the following substances including the dialyzed product 1 were charged in predetermined amounts. Dialysis product 1: 500g Sodium hydroxide: 75g Water: 1,500g

[0151] The mixture was heated to 140°C under stirring and held for 2 hours, then cooled to 70°C, and air was blown in at 500 mL / min for 3 hours. The resulting solution was powdered using a spray dryer to obtain highly modified lignin derivative C (methoxy group content: 9.7% by mass, extractable component content: 0.2% by mass, extractable component content / methoxy group content: 0.02, sulfur content of sulfo group: 5.6% by mass, total decomposition product yield by nitrobenzene oxidation: 7.1%).

[0152] (Production Example 4) (Production of highly modified lignin derivative D) Wood chips (radiata pine) were treated with alkali based on the Kraft cooking method. The alkali treatment was carried out using a rotary reaction kettle under the following conditions: active alkali (relative to bone dry chips): 20%, sulfidity: 25%, liquid ratio: 3.2 L / kg, reaction temperature: 165°C, reaction time: 180 minutes. The reaction liquid used in the alkali treatment was prepared by dissolving sodium hydroxide and sodium sulfide in water to an active alkali concentration of 50 g / L. After the reaction, filtration was carried out to obtain the alkali-treated extract 3 as the filtrate. Carbon dioxide was passed through the alkali-treated extract 3 to lower the pH of the black liquor to 10, and primary filtration was carried out. The precipitate obtained by the primary filtration was dispersed in ion-exchanged water, and sulfuric acid was dropped to lower the pH to 2, and secondary filtration was carried out. The precipitate obtained by secondary filtration was washed with water and then dried to obtain the filtered precipitate 1. In a 1L separable flask equipped with a thermometer, a stirrer, and a reflux condenser, 500 parts of a solution of dried filtered precipitate 1 dissolved in 40% NaOH at pH 10 to a solid content of 17%, 17 parts of sodium sulfite, and 12 parts of a 37% formaldehyde solution were charged and reacted for 24 hours at 95 ° C. under stirring. After cooling to room temperature, the resulting solution was powdered with a spray dryer to obtain a highly modified lignin derivative D (methoxy group amount: 10.1 mass%, extractable component amount: 1.0 mass%, extractable component amount / methoxy group amount: 0.10, S content of sulfo group: 4.4 mass%, total decomposition product yield by nitrobenzene oxidation: 4.7%).

[0153] (Production Example 5) (Production of highly modified lignin derivative E) Wood chips (radiata pine) were alkali-treated based on the soda cooking method. The alkali treatment was carried out using a rotary reaction kettle under the following conditions. Sodium hydroxide was added to the rotary reaction kettle containing the chips so that the solid content of the chips was 25 w / w% and anthraquinone was added to the solid content of the chips at 0.02 w / w%, and ion-exchanged water was added so that the liquid ratio was 5.0 L / kg. Next, steam was blown in while rotating, and the temperature was raised to 160°C, and the reaction was carried out for 4 hours. After the reaction, filtration was carried out, and alkali-treated extract 4 was obtained as the filtrate. Sulfuric acid was dropped into alkali-treated extract 4 to lower the pH to 2, and filtration was carried out. The precipitate obtained by filtration was washed with water and then dried to obtain filtered precipitate 2. In a 1L separable flask equipped with a thermometer, a stirrer, and a reflux condenser, 500 parts of a solution of dried filtered precipitate 2 dissolved in 40% NaOH at pH 10 to a solid content of 17%, 8.5 parts of sodium sulfite, and 6.0 parts of a 37% formaldehyde solution were charged and reacted for 24 hours at 95 ° C. under stirring. After cooling to room temperature, the resulting solution was powdered with a spray dryer to obtain a highly modified lignin derivative E (methoxy group amount: 10.6 mass%, extractable component amount: 1.0 mass%, extractable component amount / methoxy group amount: 0.09, sulfo group S content: 3.0 mass%, total decomposition product yield by nitrobenzene oxidation: 3.7%).

[0154] (Production Example 6) (Production of highly modified lignin derivative F) In a 1L separable flask equipped with a thermometer, a stirrer, and a reflux condenser, 500 parts of a solution obtained by dissolving the same dried filtered precipitate 2 obtained in Production Example 5 in 40% NaOH at pH 10 to a solid content of 17%, 2.1 parts of sodium sulfite, and 1.5 parts of a 37% formaldehyde solution were charged and reacted for 24 hours at 95 ° C. under stirring. After cooling to room temperature, the resulting solution was powdered with a spray dryer to obtain a highly modified lignin derivative F (methoxy group amount: 11.2 mass%, extractable component amount: 1.1 mass%, extractable component amount / methoxy group amount: 0.10, S content of sulfo group: 0.4 mass%, total decomposition product yield by nitrobenzene oxidation: 3.5%).

[0155] (Production Example 7) (Production of Lignosulfonate A) The filtrate 1 obtained in Production Example 1 was concentrated with a rotary evaporator until the solid content was 50%. The pH of the solution was then adjusted to pH 4.5 with NaOH, and powdered with a spray dryer. The obtained powder was dissolved in water to prepare an aqueous solution with a solid content of 25%, and dialyzed for 3 days using a dialysis membrane (molecular weight fraction: 20,000, Spectra / Pore cellulose ester dialysis tube). The solution in the dialysis tube was collected, concentrated until the original solution volume was 25%, and powdered with a spray dryer to obtain lignin sulfonate A (methoxy group amount: 11.1% by mass, extract component amount: 0.03% by mass, extract component amount / methoxy group amount: 0.003, S content of sulfo group: 6.7% by mass, total decomposition product yield by nitrobenzene oxidation: 16.0%).

[0156] (Production Example 8) (Production of Lignosulfonate B) Ligninsulfonate B was obtained in the same manner as in Production Example 7, except that the number of days for dialysis was changed from 3 days to 2 days (methoxy group content: 9.8% by mass, extract component content: 0.008% by mass, extract component content / methoxy group content: 0.0008, S content of sulfo groups: 6.9% by mass, total decomposition product yield by nitrobenzene oxidation: 16.2%).

[0157] Example 1 (Active material dispersibility test 1) The highly modified lignin derivative A obtained in Production Example 1 was added to water so that the solid content was 0.17% by mass. Then, SiOx (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KSC-1064) as a silicon-based negative electrode active material was added to 3.2% by mass, and the mixture was stirred at 2500 rpm for 30 minutes using a homodisper to obtain a dispersion. The average particle size of SiOx in the dispersion was measured using a Zetasizer 3000HSA (manufactured by Malvern). The measurement results of the average particle size and the dispersion state immediately after stirring are shown in Table 1.

[0158] (Examples 2 to 8) Active material dispersibility test 1 was carried out in the same manner as in Example 1, except that the highly modified lignin derivatives B to F or lignin sulfonates A and B obtained in Production Examples 2 to 8 were used instead of the highly modified lignin derivative A obtained in Production Example 1, respectively.

[0159] Comparative Example 1 Active material dispersibility test 1 was performed in the same manner as in Example 1, except that carboxymethyl cellulose (manufactured by Nippon Paper Industries Co., Ltd., MAC500LC) (DS value: 0.65 mol / C6, 1% viscosity: 4700 mPa s) was used instead of the highly modified lignin derivative A obtained in Production Example 1.

[0160] (Reference example 1) Active material dispersibility test 1 was carried out in the same manner as in Example 1 except that no dispersant was used. However, because separation occurred, it was not possible to measure the average particle size.

[0161] [Table 1]

[0162] As shown in Table 1, the dispersants of Examples 1 to 8 dispersed SiOx well in water. The highly modified lignin derivatives and lignin sulfonates of each Example were introduced with a sulfo group at a predetermined sulfo group S content, and thus maintained high water solubility. It is presumed that they exhibited excellent dispersion performance by efficiently adsorbing to SiOx in water. The carboxymethylcellulose of Comparative Example 1 also showed dispersibility in SiOx, but the average particle size of SiOx was larger than that of Examples 1 to 8. Carboxymethylcellulose is used for the purpose of improving the dispersibility of the negative electrode active material and for the purpose of imparting a certain viscosity to the active material slurry and efficiently binding the active material and the current collector, but it can be seen that the highly modified lignin derivatives A to F and the lignin sulfonates A and B are more suitable as dispersants for SiOx, which is a silicon-based negative electrode active material.

[0163] Example 9 (Production of negative electrode mixture composition) The silicon-based negative electrode active material was SiOx (Shin-Etsu Chemical Co., Ltd., product name: KSC-1064), and the conductive additive was acetylene black (Stream Chemical Co., Ltd., 50% compressed), carboxymethylcellulose (manufactured by Nippon Paper Industries Co., Ltd., MAC500LC) (DS value: 0.65 mol / C6, 1% viscosity: 4700 mPa·s), highly modified lignin derivative A obtained in Production Example 1 as a dispersant (methoxy group amount: 11.9 mass%, extractable component amount: 0.7 mass%, extractable component amount / methoxy group amount: 0.06, sulfur content of sulfo group: 1.6 mass%, total decomposition product yield by nitrobenzene oxidation: 7.1%), and styrene butadiene rubber (SBR, manufactured by ENEOS Materials Co., Ltd., product number TRD104A) were mixed so that the solid content mass ratio was 97:0.5:0.67:0.33:1.5, water was added so that the slurry concentration was 45.6 mass%, and the mixture was thoroughly stirred using a Mazerustar (manufactured by Kurabo Industries, KK-250S) to obtain a slurry-like negative electrode mixture composition.

[0164] (Preparation of negative electrode plate) This slurry-like negative electrode mixture composition was applied to a copper foil (NC-WS, manufactured by Furukawa Electric Co., Ltd.) measuring 320 mm in length, 170 mm in width, and 17 μm in thickness using an applicator, and then air-dried for 30 minutes, and then dried in a dryer at 60° C. for 30 minutes. It was then pressed using a small tabletop roll press (SA-602, manufactured by Tester Sangyo Co., Ltd.) under conditions of 5 kN and a roll peripheral speed of 50 m / min to obtain a coating weight of 19.7 g / m 2 Thus, a negative electrode plate with an effective discharge capacity of 2100 mAh / g was obtained.

[0165] (Production of coin-type lithium-ion secondary batteries) The obtained negative electrode plate and the LiCoO2 positive electrode plate (manufactured by NEI, coating weight 20.56 mg / cm 2 , capacity 3mAh / cm 2 ) was punched out into a circle having a diameter of 16 mm, and the punched negative and positive electrode plates were vacuum dried at 120°C for 12 hours. Similarly, a separator (manufactured by CS Tech, a polypropylene separator having a thickness of 20 μm) was punched out to have a diameter of 17 mm, and vacuum dried at 60° C. for 12 hours. Then, the negative electrode plate was placed in a stainless steel circular dish-shaped container with a diameter of 20.0 mm, and then a separator, a positive electrode plate, a spacer (diameter 15.5 mm, thickness 1 mm), and a stainless steel washer (manufactured by Hosen Co., Ltd.) were stacked in this order, and then 300 μL of electrolyte (1 mol / L LiPF6, ethylene carbonate and diethyl carbonate volume ratio 1:1) was added to the circular dish-shaped container. A stainless steel cap was placed over this via a polypropylene packing, and the container was sealed with a coin battery crimping machine (Hosen Co., Ltd.) to obtain a coin-shaped lithium-ion secondary battery.

[0166] A charge / discharge rate test was carried out on the obtained battery, and the discharge capacity was measured and the capacity retention rate was calculated.

[0167] (Examples 10 to 16) The negative electrode mixture compositions were produced, the negative electrode plates were prepared, and the coin-type lithium ion secondary batteries were prepared in the same manner as in Example 9, except that the highly modified lignin derivatives B to F or the lignin sulfonates A and B were used instead of the highly modified lignin derivative A obtained in Production Example 1. The obtained batteries were also evaluated.

[0168] Comparative Example 2 In the production of the negative electrode mixture composition, a negative electrode mixture composition was produced in the same manner as in Example 9, except that the highly modified lignin derivative A was not added. In addition, SiOx (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KSC-1064) as a silicon-based negative electrode active material, acetylene black (manufactured by Stream Chemical Co., Ltd., 50% compressed) as a conductive assistant, carboxymethylcellulose (manufactured by Nippon Paper Industries Co., Ltd., MAC500LC) (DS value: 0.65 mol / C6, 1% viscosity: 4700 mPa·s), and styrene butadiene rubber (SBR, manufactured by ENEOS Materials Co., Ltd., product number TRD104A) were mixed so that the solid mass ratio was 97:0.5:1.0:1.5. Using this, a negative electrode plate was prepared in the same manner as in Example 9, and a coin-type lithium ion secondary battery was prepared. In addition, the obtained battery was evaluated.

[0169] [Table 2]

[0170] As shown in Table 2, the capacity retention rate of the battery in Examples 9 to 16, which used a dispersant containing a lignin component, was clearly improved compared to the battery in Comparative Example 2. In Examples 9 to 16, it is presumed that the negative electrode active material SiOx was uniformly dispersed in the electrode, and other components effectively buffered the volume change of the negative electrode active material during cycling, thereby suppressing irreversible capacity loss due to electrical interruption.

[0171] As shown in Table 2, compared with the batteries using the highly modified lignin derivatives A to F of Examples 9 to 14, which have a low S content in the sulfo group, a high content of extractables, and a low total yield of decomposition products due to nitrobenzene oxidation, the battery using lignin sulfonate A of Example 15, which has a high S content in the sulfo group, a low amount of extractables, and a high total yield of decomposition products due to nitrobenzene oxidation, had a lower capacity retention rate. The battery using lignin sulfonate B of Example 16, which has a lower amount of extractables than lignin sulfonate A, had a slightly lower capacity retention rate. In order to investigate the cause of the different degrees of improvement in battery performance in each Example, the differences in the active material dispersion performance of the highly modified lignin derivatives A to F and the lignin sulfonates A and B were compared in detail using a Zetasizer. Carboxymethylcellulose (manufactured by Nippon Paper Industries Co., Ltd., MAC500LC) (DS value: 0.65 mol / C6, 1% viscosity: 4700 mPa·s) was also used at the same time to approximate the composition of the negative electrode mixture composition.

[0172] (Example 17) (Active material dispersibility test 2) An aqueous solution was prepared with carboxymethylcellulose (manufactured by Nippon Paper Industries Co., Ltd., MAC500LC) (DS value: 0.65 mol / C6, 1% viscosity: 4700 mPa·s) at a solid content of 0.17 mass%, and the highly modified lignin derivative A obtained in Production Example 1 at a solid content of 0.12 mass%. Then, SiOx (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KSC-1064) was added to a solid content of 3.2 mass%, and the mixture was stirred at 2500 rpm for 30 minutes using a homodisper to obtain a dispersion. The average particle size of SiOx in the dispersion was measured using a Zetasizer 3000HSA (manufactured by Malvern). The measurement results of the average particle size and the dispersion state immediately after stirring are shown in Table 3.

[0173] (Examples 18 to 24) Active material dispersibility test 2 was carried out in the same manner as in Example 17, except that the highly modified lignin derivatives B to F or lignin sulfonates A and B obtained in Production Examples 2 to 8 were used instead of the highly modified lignin derivative A obtained in Production Example 1, respectively.

[0174] [Table 3]

[0175] As shown in Table 3, in Examples 23 and 24 in which lignin sulfonate was used under the condition of using CMC in combination and dispersant addition rate of 3.5 mass% relative to SiOx, the particle size of SiOx was larger than that of Examples 17 to 22 in which a highly modified lignin derivative was used. Since the lignin sulfonate used in Examples 23 and 24 has a higher S content in the sulfo group than the highly modified lignin derivative used in Examples 17 to 22, it is presumed that the lignin derivative with a lower S content in the sulfo group is more adsorbed to SiOx and exhibits high dispersing performance, although the detailed mechanism is unknown. For the above reasons, it is presumed that the improvement effect of the capacity retention rate was relatively small in Examples 15 and 16 in which lignin sulfonate was used, as shown in Table 2.

Claims

1. A composition for a negative electrode of a secondary battery, comprising: a silicon-based negative electrode active material; and a dispersant, the dispersant containing a lignin component including a lignin derivative, the lignin derivative having a functional group represented by the following formula (1), and an S content in the functional group being 0.1 to 7.0 mass %. Formula (1): -SO 3 M (In the formula, M represents a hydrogen atom, a monovalent metal, or a divalent metal.)

2. 2. The negative electrode composition according to claim 1, wherein the lignin component has a weight average molecular weight of 6,000 to 35,000, and a value obtained by dividing the weight average molecular weight by the number average molecular weight is 1.5 to 3.

1.

3. The amount of extracted components per solid content of the lignin component is 0.01 to 2.5% by mass, The amount of methoxy groups per solid content of the lignin component is 3 to 18% by mass, 3. The negative electrode composition according to claim 1, wherein a mass ratio of an amount of the extracted component per solid content of the lignin component to an amount of methoxy groups is 0.001 to 0.

25.

4. 3. The negative electrode composition according to claim 1, wherein a total decomposition product yield by alkaline nitrobenzene oxidation is 15% or less per solid content of the lignin component.

5. 3. A negative electrode for a secondary battery comprising a negative electrode active material layer containing the negative electrode composition according to claim 1, a negative electrode binder, and a conductive assistant.

6. A secondary battery comprising the negative electrode according to claim 5 .

7. 3. The negative electrode composition according to claim 1, wherein the secondary battery is a lithium ion battery.

Citation Information

Patent Citations

  • Negative electrode composite material for lithium ion battery and preparation method of negative electrode composite material

    CN104538609A

  • Silica / lignin porous carbon composite material, preparation method thereof and application in lithium ion battery anode material

    CN108878813A

  • Lithium battery conductive paste and preparation method thereof

    CN110518248A

  • Silicon-carbon negative electrode material, lithium ion battery negative electrode and lithium ion battery

    CN110797512A

  • Carbon-coated silicon oxide / graphite composite particles, manufacturing method, and uses thereof

    JP2020527283A